EFFORTS TO IMPROVE STUDENTS' POETRY WRITING ABILITY THROUGH POETRY LEARNING USING DEMONSTRATION TECHNIQUES, INVOLVEMENT AND MENTORING GRADE XI (Case study at SMA Negeri Ligung 1 Majalengka Regency) - Budiana Budiana (Eduvis : Jurnal Manajemen Pendidikan Islam, 2021)
Research is a derivative of Vygotsky's constructivism theory. In the descent, the researcher took a model that constructed the students' thinking. The model is demonstration, involvement, and mentoring. This model is used to examine the effect of learning on Indonesian subjects in writing poetry. The school that is being tested is SMA Negeri Ligung 1 class XI. With consisting of a control class of 30 students and an experimental class of 30 students. The research approach used is qualitative with experimental methods. The results obtained from this study were an increase in the score of the ability to write essays on the pretest and posttest. The pretest average score was 43, while the posttest average score was 50.So, the ability to write essays in the control class of SMA Negeri 1 Ligung increased by 7. Whereas in the experimental class, the score data on the ability to write essays on the pretest and posttest was found. . The average score for the pretest was 44, while the average score for the posttest was 79. So, the ability to write essays in the experimental class at SMA Negeri Ligung 1 has increased by 35 Abstrak Penelitian merupakan turunan dari teori kontruktivisme yang dimunculkan oleh Vygotsky. Dalam turunanya peneliti mengambil satu model yang mengontruksikan cara berpikir siswa. Model itu adalah demostrasi, pelibatan, dan pendampingan. Model ini digunakan untuk meneliti pengaruh pembelajaran pada mata pelajaran bahasa Indonesia materi menulis puisi. Adapun sekolah yang menjadi ujicoba adalah SMA Negeri Ligung 1 kelas XI. Dengan tediri kelas kontrol sebanyak 30 siswa dan kelas eksperimen sebanyak 30 siswa. Pendekatan penelitian yang digunakan adalah kualitatif dengan metode eksperimen. Hasil yang diperoleh dari penelitian tersebut adalah Terjadi peningkatan skor kemampuan menulis esai pada pretest dan posttest. Nilai rata-rata pretest adalah 43, sedangkan nilai rata-rata pada posttest adalah 50. Jadi, kemampuan menulis esai pada kelas kontrol SMA Negeri 1 Ligung mengalami kenaikan sebesar 7. Sedangkan pada kelas eksperimen di dapati data skor kemampuan menulis esai pada pretest dan posttest. Nilai rata-rata pretest adalah 44, sedangkan nilai rata-rata pada posttest adalah 79. Jadi, kemampuan menulis esai pada kelas eksperimen di SMA Negeri Ligung 1 mengalami kenaikan sebesar 35.